A Short History of the Middle East : From the Rise of Islam to Modern Times - Kirk, George E. (George Eden), 1911-1993 (London Methuen & Co. Ltd, 1957)
George Kirk is a British Archaeologist who worked in the Middle East before World War II. Owing to his expert knowledge he was engaged during the war in top level intelligence analysis in Cario. After the capitulation of Italy, he moved to Jerusalem as one of the lecturers in Colonel Bertram Thomas's Middle East Center for Arabic Studies where British navy, army, air force and civilian special service officers received a year's training in the history, customs and the principal language of the Middle East. (Incidentally, it was in this school that Aubrey Eban, now Chief Israeli Representative in the United Nations, was Chief Instructor in Arabic). It was for the courses given by Mr. Kirk in this school that much of the material for this book was originally collected. It has been supplemented by further material assembled by Mr. Kirk while preparing the Middle East sections of the series of the new volumes of the Survey of world affairs to be issued by the Royal Institute of International Affairs in London. -- From http://www.jstor.org (Oct. 12, 2016).
Include Appendix and Index
Keywords: Middle East -- Islam -- Middle East -- History -- Middle East -- History